Relationships Between Management Functions and Family Economic Status Among Kerman Households in Iran - Yadollahi, Mehdi (2011)
This study was undertaken to determine the relationships between management functions and family economic status. Management functions (independent variables) comprises of planning, organizing, coordinating, directing, and controlling;whereas family economic status, (dependent variable) comprising three dimensions of income, expenditure, and assets. The specific objectives of this research are; to determine, the economic status of the families in Kerman City, the level of managerial functions practice by the families, the relationship between the levels of managerial functions practiced and family economic status, the effect of demographic variables on family economic status, and finally, to determine the factors affecting family economic status. The head of the households are respondents of the study. The population of the study was households in Kerman City. The instruments used for this study is a set of questionnaire consisting of three sections. The first section focuses on information concerning the demographic characteristics; the second section consists of managerial functions,and the last section of the questionnaire concerns family economic status, including income, wealth and expenditure (consumption). The data collection was done through face-to-face interviews to obtain information from the heads of the households and other members of the family. The interviews were carried out betweenNovember 2008 andJanuary 2009.The areas and respondents were selected by cluster random sampling. The sample consists of 390 households from five areas in Kerman City, Iran. The quantitative data was analysed using various descriptive and correlation statistics,including chi-square, independent sample t-test, Pearson product moment correlation, Spearman rho, and multinomial logistic regression. Regarding Kerman’s family economic status, findings revealed that Kerman families’ economic status is higher than averageIranian families. The findings of the study support the relationship between management functions and family economic status. Management functions, namely, planning, organizing, coordinating, directing, and controlling could be used to predict family economic status dimensions, namely, income, expenditure, and assets. Also, the findings of the study revealed that demographic variables, i.e. age, level of education, and occupation have significant correlations with family economic status. The results of this study will be especially interesting to policy makers, teachers and students, family services agencies, professionals, non-government organizations and heads of the households. Limitations of the study include the difficulty inobtaining information concerning the economic status of the families. For future research, the replication of the study could be carried out to other societies or countries such as Malaysia. Further research is also needed to develop a new model and to identify the relationship between lifestyle or household leadership styles and family economic status.